Blood pressure, lipid profile and glycemic control among type-2 diabetic patients in North Kerala - Kavuparambil, Liji; Pammi, Ashok Kumar; Kattil, Jithesh Tharayil; Kaliyaperumal, Santha; Kollathodi, Shifa (International Journal of Research in Medical Sciences, 2021)
Background: Glycemic control, lipid control and other modifiable risk factor, is very important to prevent complications of type 2 diabetes. The objective of this study was to analyze glycemic control, lipid profile, BP and find the correlation of these parameters in the diabetic population of North Kerala. Methods: This was a cross sectional study among the type 2 diabetic patients with 40-60 years of age, and those without any cardiac, renal, liver, and thyroid dysfunction. Fasting blood sugar, BP, HbA1c and lipid profile were assessed by VITROS 5600 integrated system. The study population was grouped in to two based on their glycemic control (HbA1c ≥7% and HbA1c <7%). Statistical analysis was performed by SPSS software. The comparison of variables age, BP, FBS, HbA1c, total cholesterol, LDL, HDL, TG, and TG/HDL was tested using independent student t test. The correlations between the variables were analyzed using Pearson correlation coefficient. P values less than 0.05 were considered significant. Results: There was a significant positive correlation between DBP and poor glycemic control group (t=2.35, p=0.0102). Fasting blood sugar (p≤0.00001), total cholesterol (p=0.0031), triglycerides (p≤0.00001), LDL (p=0.0051), HDL (p=0.0010) and TG/HDL (p≤0.00001) also were significantly higher in this group. Age or gender showed no correlation with HbA1c and BP. Conclusions: This study shows highly significant positive correlation between TG/HDL and poor glycemic control. It appears the degree of hypertension is not correlated with HbA1c, but significantly correlated with lipid profile especially among those with poor glycemic control.